Software quality for the certified software development associate - Towhidnejad, Massood (IEEE, 2012)
This tutorial is part of a series of eLearning courses designed to help you prepare for the examination to become a Certified Software Development Associate (CSDA) or to learn more about specific software engineering topics. Courses in this series address one or more of the fifteen Knowledge Areas that comprise the Software Engineering Body of Knowledge - or SWEBOK, upon which the Certification Exam is based. This course is intended to assess your understanding of software requirements through inline quizzes and feedback. The CSDA credential is intended for graduating software engineers and entry-level software professionals and serves to bridge the gap between your educational experience and real-world work requirements. This knowledge area deals with software quality considerations which transcend the life cycle processes. Software quality is a ubiquitous concern in software engineering, and so it is also considered in many of the other SWEBOK Knowledge Areas